Food Ingredients Involved in White-to-Brown Adipose Tissue Conversion and in Calorie Burning - El Hadi, Hamza; Di Vincenzo, Angelo; Vettor, Roberto; Rossato, Marco (Frontiers in Physiology, 2019)
Obesity is the consequence of chronic positive energy balance and considered a leading risk factor for cardiovascular and metabolic diseases. Due to its epidemic trends among children and adults, there is an increasing interest in implementing new therapeutic interventions to tackle overweight and obesity. Activation of brown adipose tissue (BAT) represents today a promising strategy to enhance energy expenditure (EE) through heat production. More recently, ‘browning’ of white adipose tissue (WAT) has gained increasing attention in research area as an alternative method in stimulating energy dissipation. This minireview aims to summarize the current knowledge of some dietary compounds that have been shown to promote BAT activation and WAT browning with subsequent beneficial health effects.